Mucosal Delivery of Fusion Proteins with Bacillus subtilis Spores Enhances Protection against Tuberculosis by Bacillus Calmette-Guérin - Copland, Alastair; Diogo, Gil R.; Hart, Peter; Harris, Shane; Tran, Andy C.; Paul, Mathew J.; Singh, Mahavir; Cutting, Simon M.; Reljic, Rajko (Frontiers in Immunology, 2018)
Tuberculosis (TB) is the most deadly infectious disease in existence, and the only available vaccine, Bacillus Calmette-Guérin (BCG), is almost a century old and poorly protective. The immunological complexity of TB, coupled with rising resistance to antimicrobial therapies, necessitates a pipeline of diverse novel vaccines. Here, we show that B. subtilis spores can be coated with a fusion protein (‘FP1’) consisting of M. tuberculosis (Mtb) antigens Ag85B, ACR and HBHA. The resultant vaccine, Spore-FP1, was tested in a murine low-dose Mtb aerosol challenge model. Mice were primed with subcutaneous BCG, followed by mucosal booster immunisations with Spore-FP1. We show that Spore-FP1 enhanced pulmonary control of Mtb, as evidenced by reduced bacterial burdens in the lungs. This was associated with elevated antigen-specific IgG and IgA titres in the serum and lung mucosal surface, respectively. Spore-FP1 immunisation generated superior antigen-specific memory T-cell proliferation in both CD4+ and CD8+ compartments, alongside bolstered Th1-, Th17- and Treg-type cytokine production, compared to BCG immunisation alone. CD69+CD103+ tissue resident memory T-cells (Trm) were found within the lung parenchyma after mucosal immunisation with Spore-FP1, confirming the advantages of mucosal delivery. Our data show that Spore-FP1 is a promising new TB vaccine that can successfully augment protection and immunogenicity in BCG-primed animals.